The functioning of intertextual references and the consequences of remediation of the Western genre in Call of Juarez - Szczęsny, Tomasz (Replay. The Polish Journal of Game Studies, 2014)
The author tries to examine the reasons for the popularity of the Western film convention manifested by the game Call of Juarez. It seems surprising because Western – once a popular genre – currently seems to be almost extinct. The key to the investigation of Call of Juarez appears to be the analysis of the intertextual references and the remediation of the Western convention. In order to explain the popularity of Western themed games, the author argues that the reasons responsible for the death of Western were mainly economic and not as it was previously considered – sociological.